Influence of Brand Image and Price on Purchase Decision: Study on Fashion Consumers Distro in Bandung - Ranggi Fauzul Adzim Apip Nugraha; Haris Nurdiansyah (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2022)
This study aims to determine the influence of brand image and price on the purchasing decisions of fashion consumers at one of the distros in the city of Bandung. The research method used is the Quantitative method with the Verification approach, the samples taken in this study are consumers who have purchased a product with as many as 100 respondents with the accidental sampling technique. Furthermore, primary data uses to obtain supporting data and information, namely data obtained directly from consumers. Based on research using path analysis, the brand image variable has a direct effect of 22.8%, an indirect effect through the price relationship of 13.1%, and the total effect is 35.9%. The price variable has a direct effect of 14.1% and an indirect effect through the brand image relationship of 13.1%; the total effect is 27.1%. The research results on the correlation coefficient of determination illustrate the magnitude of the contribution of all independent variables, namely brand image and price, in determining the purchasing decision variable, which is 0.630 or 63%. In comparison, other factors that influence purchasing decisions that are not examined are 36.9%. The implications of the research results are for fashion businesses to pay more attention to brand image and price to improve purchasing decisions.